2010
DOI: 10.1194/jlr.m009258
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of electronegative low-density lipoprotein

Abstract: This article is available online at http://www.jlr.org LDL, the main cholesterol carrier in plasma, is composed of approximately 75% lipid (mainly cholesterol) and 25% protein. The major protein in LDL is apolipoprotein B-100 (apoB-100), a protein of 550 kDa that accounts for more than 95% of the total protein mass in LDL ( 1 ). However, minor amounts of other apolipoproteins associated to LDL have been reported. Several of these proteins, such as apoE, apoC-III, and platelet-activating factor acetylhydrolase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 36 publications
2
59
0
4
Order By: Relevance
“…We used a dualspecific ELISA in which antibodies to apoD bound intact apoB-containing lipoproteins equally efficient as antibodies specific for apoB. This property was unique for apoD and was not seen with other exchangeable apolipoproteins such apoE, apoH and apoJ, all of which are present in HDL and LDL/VLDL lipoprotein particles [32,33,34]. Adding detergent inhibited the apoD-mediated binding of apoB, demonstrating that changes in the LDL structure affect the formation of the complex.…”
Section: Discussionmentioning
confidence: 99%
“…We used a dualspecific ELISA in which antibodies to apoD bound intact apoB-containing lipoproteins equally efficient as antibodies specific for apoB. This property was unique for apoD and was not seen with other exchangeable apolipoproteins such apoE, apoH and apoJ, all of which are present in HDL and LDL/VLDL lipoprotein particles [32,33,34]. Adding detergent inhibited the apoD-mediated binding of apoB, demonstrating that changes in the LDL structure affect the formation of the complex.…”
Section: Discussionmentioning
confidence: 99%
“…The most abundant proteins in LDL(-) are apoA-I (0.15 molecules/particle of LDL(-)), apoE (0.22), apoC-III (0.37) and apoA-II (0.14), with a content 3-5 fold higher in LDL(-) than in native LDL (Bancells, 2010a). The role of these proteins is unclear but their relevance is probably low.…”
Section: Proteinsmentioning
confidence: 99%
“…The role of these proteins is unclear but their relevance is probably low. However, other proteins whose absolute content in LDL(-) is lower, such as apoF (0.06 molecules/particle), apoJ (0.01) or PAF-AH (0.004) (Bancells, 2010a;, but their relative content compared with native LDL is 10, 20 and 100-fold higher, respectively, could have a much more relevant role. ApoF is the physiological inhibitor of cholesteryl ester transfer protein (Morton, 2008), a protein that regulates the catabolism of the VLDL-IDL-LDL cascade.…”
Section: Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteomic analysis, performed by LC MS/MS method, revealed the presence of 28 proteins most of which were involved in inflammation, coagulation and innate immunity, besides apolipoproteins involved in lipid metabolism. They observed that electronegative LDL, a minor subfraction of LDL fraction, has a higher content of minor proteins, especially apo F and apo J, compared to electropositive LDL (Bancells et al, 2010). Collins et al performed a proteomic analysis, applying LC MS/MS, to compare the lipoprotein-associated proteins derived from plasma and serum samples.…”
Section: Ldlmentioning
confidence: 99%